The Impact of Fear of Better Options (FOBO) on Consumer Purchase Intention - Cruz, David Manuel Ascensão (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Marketing Intelligence